Methodological Approaches to Societies in Transformation How to Make Sense of Change - Berriane, Yasmine; Derks, Annuska; Kreil, Aymon; Lüddeckens, Dorothea (Anthropology, Change, and Development, 2021)
XIII, 282 p. 5 illus., 4 illus. in color.